Liquid metal-based electrosynthesis of stratified zinc–organic frameworks. Issue 40 (13th September 2022) - Zheng, Jiewei; Mousavi, Maedehsadat; Baharfar, Mahroo; Sharma, Astha; Kumeria, Tushar; Han, Jialuo; Kumar, Priyank; Kalantar-Zadeh, Kourosh; Mayyas, Mohannad
Abstract : Post-transition metal-based liquid alloys are emerging as media for undertaking chemical reactions. Abstract : Post-transition metal-based liquid alloys are emerging as media for undertaking chemical reactions. When dissolved in such media, solute metals become highly reactive, making chemical reactions that involve these metals more efficient. Here we investigate liquid alloys for the synthesis of zinc–organic frameworks. This is achieved by anodizing a gallium–zinc liquid alloy immersed in a mixture solution of an organic linker and an aprotic electrolyte. Density functional theory calculations indicate that the zinc atoms, in the gallium–zinc system, are reactive and have a high tendency to ionize. Our liquid metal-based approach produces a unique stratified structure of the zinc–organic framework under mild conditions of near room temperature, low potentials, and short reaction times. Finally, as a proof-of-concept, the implementation of a continuous liquid metal-based reactor to synthesize a stratified zinc-organic framework is demonstrated. Overall, this study demonstrates the attractive features of liquid metals for enabling efficient and scalable production of stratified metal–organic frameworks.